2011
DOI: 10.3390/d3040547
|View full text |Cite
|
Sign up to set email alerts
|

Diversity of Pharmacological Properties in Chinese and European Medicinal Plants: Cytotoxicity, Antiviral and Antitrypanosomal Screening of 82 Herbal Drugs

Abstract: Abstract:In an extensive screening, the antiviral, antitrypanosomal and anticancer properties of extracts from 82 plants used in traditional Chinese medicine and European phytomedicine were determined. Several promising plants that were highly effective against hepatitis B virus (HBV), bovine viral diarrhoea virus (BVDV)-a flavivirus used here as a surrogate in vitro model of hepatitis C virus, trypanosomes (Trypanosoma brucei brucei) and several cancer cell lines were identified. Six aqueous extracts from Cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(29 citation statements)
references
References 91 publications
0
26
0
1
Order By: Relevance
“…b . brucei line was obtained from Prof. Peter Overath (Max‐Planck‐Institut für Biologie, Tübingen, Germany) and has been cultured in our department of IPMB since 1999 . Trypanosoma brucei brucei was maintained in complete Baltz medium .…”
Section: Methodsmentioning
confidence: 99%
“…b . brucei line was obtained from Prof. Peter Overath (Max‐Planck‐Institut für Biologie, Tübingen, Germany) and has been cultured in our department of IPMB since 1999 . Trypanosoma brucei brucei was maintained in complete Baltz medium .…”
Section: Methodsmentioning
confidence: 99%
“…Artemisia is a diverse genus of plants with 400 species belonging to the family Asteraceae, with most herbs having strong aromas and bitter tastes arising from the presence of terpenoids and sesquiterpene lactones (Herrmann et al, 2011). The representative species of the Artemisia are Artemisia annua Linne and Artemisia capillaris Thunberg.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, Arctium lappa (Asteraceae), also known as burdock, is a medicinal plant popularly used as hepatoprotective, antiseptic and anti-inflammatory that has provided biologically activity compounds, mainly lignans, against some parasites, such as Trypanosoma cruzi [13]. Furthermore, it was shown that the fruits extract of A. lappa improved kidney function in mice infected with S. haematobium [14].…”
Section: Introductionmentioning
confidence: 99%